Isometric growth in the world's largest bony fishes (genus Mola)? Morphological insights from fisheries bycatch data. (6th September 2018) - Phillips, Natasha D.; Kubicek, Lukas; Payne, Nicholas L.; Harrod, Chris; Eagling, Lawrence E.; Carson, Carol D.; Cappanera, Valentina; Houghton, Jonathan D.R.
Abstract: For teleost fishes, the relationship between morphometric traits can provide significant insight into species life history, however gathering such data for noncommercial species can prove challenging. Here, we use data collected opportunistically from fisheries bycatch and stranding events to assess growth scaling over orders of magnitude in the ocean sunfish (genus Mola). Intriguingly, the confidence intervals for the relationship between length and mass suggests that isometric scaling is likely, a growth pattern rarely observed in fishes owing to the scaling of supportive structures. These data also enabled assessment of geometric morphometrics, which indicated that Mola sp shape varies subtly but significantly ontogenetically, with increased fin area comparative to body area as fish increase in size. More practically, total length emerged as an effective predictor for a range of morphological traits, including mass, fin lengths and surface area, which can provide vital baseline data for fisheries modeling and management. Abstract : Trash to treasure: morphometric data from ocean sunfish bycatch provides baseline information for fisheries management and new insights into the growth scaling of one of the largest bony fishes, with potential isometric scaling of mass with length.